Women and the Da'wah Movement: Historical Analysis of the Khadijah RA’s Role in the Time of Rasulullah Saw - Agus Riyadi; Saerozi Saerozi; Fania Mutiara Savitri (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2021)
This study aims to provide an overview of the ideal woman's figure as a husband's companion in carrying out da'wah activities. Specifically, the research is directed to explore the historical roots of Khadijah RA's role in the da'wah activities of the Prophet Muhammad. The research was conducted with a qualitative approach through history and literature studies. The results showed that the role of Khadijah RA in the da'wah of the Prophet Muhammad was carried out in two forms. Spiritually, Khadijah RA strengthened the belief and mentality of the Prophet Muhammad in receiving and spreading the message of Islam. Materially, Khadijah strengthened the da'wah of the Prophet by building trade relations and marital ties, elevating the living conditions of the Prophet Muhammad's welfare, and appearing to play a role both with energy, mind, and wealth. This research has implications for efforts to build commitment, consistency, and collaboration of women's da'wah. Moreover, it is useful to respond global challenges and strengthen Islamic da'wah activity in Indonesia for personal, family, and institutional scopes.Penelitian ini menggambarkan figur seorang wanita ideal sebagai pendamping suami dalam melaksanakan kegiatan dakwah. Secara spesifik, penelitian diarahkan dengan menggali akar historis peran Khadijah RA dalam kegiatan dakwah Rasulullah Saw. Penelitian dilakukan dengan pendekatan kualitatif melalui studi historis dan kepustakaan. Hasil penelitian menunjukkan bahwa peran Khadijah RA dalam dakwah Rasulullah Saw dilakukan dalam dua bentuk. Secara spiritual, Khadijah RA memperkuat keyakinan dan mentalitas Rasulullah Saw dalam menerima dan menyebarkan risalah Islam. Secara material, Khadijah memperkuat dakwah Rasulullah dengan cara membangun hubungan dagang dan ikatan perkawinan, mengangkat kondisi kesejahteraan nabi Muhammad Saw dan tampil memberikan peranan secara tenaga, pikiran maupun harta kekayaannya. Penelitian ini berimplikasi terhadap upaya membangun komitmen, konsistensi dan kolaborasi dakwah perempuan dalam memperkuat aktivisme dakwah Islam di Indonesia baik dalam ruang lingkup personal, keluarga dan kelembagaan.